The Socio-economic Costs of Crime and Violence in Papua New Guinea : Recommendations for Policy and Programs - Lakhani, Sadaf; Willman, Alys M. (World Bank, Washington, DC, 2014)
At the request of the Prime Minister's office, between 2011-2013, the World Bank conducted a study to understand the social and economic costs of crime and violence in Papua New Guinea. The purpose of the study was to feed a national conversation about crime and violence and inform policy directions and program interventions. The findings of the study are summarized in this research and dialogue series. This brief outlines the policy and programming recommendations that emerge from the research. The recommendations are intended to provide information, possible policy approaches towards an ongoing dialogue on the issue of crime and violence and that they will fuel a growing coalition of state and civil society actors for an integrated response.